The International Law of Protection and Promotion of Human Rights: Past, Present and Future (Part I) - D. V. Ivanov; E. V. Tarasyants (Московский журнал международного права, 2009)
The International Law of Protection and Promotion of Human Rights is one of the branches of the contemporary International Law including legal rules that regulate interstate cooperation in respect of creation of international instruments on human rights and mechanisms of control and protection of human rights. The branch of International Law in question has quite a long history and is still in process of development nowadays. Thus this subject remains one of the most urgent issues. The present article concerns first of all the review of human rights concepts as well as the notion of the branch, generations of human rights and principals of the branch; regional and universal international human rights law sources; international mechanisms for protection of human rights including the new mechanism created within United Nations (Human Rights Council and its new procedures); new trends in development of International Human Rights Law (new human rights, rights of indigenous peoples, reform of UN human rights protection mechanism, extension of international courts’ competence, humanitarian intervention etc.) including situation with human rights in Russia.